NAVIGATING ECONOMIC TURBULENCE: EXCHANGE RATE VOLATILITY AND MACROECONOMIC RESILIENCE IN OPEN ECONOMIES - Kholilatul Khusni; Opiefah Nurviliza (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Exchange rate volatility significantly impacts developing countries' macroeconomic stability in the global economy. This study investigates the effects of exchange rate fluctuations on key macroeconomic indicators, focusing on Indonesia. Using a qualitative descriptive approach with secondary data from institutional sources and an OLS regression analysis, the research examines the challenges faced by developing nations. Findings reveal that exchange rate volatility substantially influences inflation, economic growth, foreign exchange reserves, and the balance of payments. The Indonesian case study (2013, 2018, and 2022–2023) demonstrates that external factors, particularly global monetary policy changes and geopolitical tensions, primarily drive exchange rate pressures. Short-term policy responses, including adjustments to the BI-7 Day Reverse Repo Rate and foreign exchange market interventions, have proven effective for immediate stability. However, long-term macroeconomic resilience necessitates comprehensive strategies such as economic diversification, institutional strengthening, and sustained policy coordination to mitigate the impacts of exchange rate volatility in developing countries.